EMOTIONAL INTELLECT OF POLICE: CONTENTS OF THE CONCEPT, ITS STRUCTURE, TYPES AND MODELS (Psychology Travelogs, 2023)
It is clarified that the concept of "emotional intelligence" includes a set of intellectual and affective processes which are reflected in the definition of this term depending on different scientific approaches. Based on the results of the analysis of scientific approaches to the interpretation of the term "emotional intelligence", it is determined that it is defined comprehensively as: the ability of a police officer to understand interpersonal relationships characterized by emotions of a different spectrum of manifestation; the ability of a police officer to manage his/her emotional sphere through intellectual synthesis and analysis to improve the thinking process; a set of personal, emotional and social competencies which affect the ability of a police officer to respond effectively to challenges and pressures from the environment.The effectiveness of a law enforcement officer's performance of his/her professional activity is determined by various factors, namely the ability to recognize not only his/her emotions but also the feelings and emotions of the opponent, to exert psychological influence on him/her, to choose the optimal model of behavior for constructive resolution of conflict situations, to build trusting and friendly interpersonal relationships, to tune in to the work process and collective work to achieve the goal together, to strive for self-development and mastery of new skills. In addition, society places high demands on the efficiency and success of police officers in performing their duties. In extreme situations where civilians may be left out, police officers need to do their job regardless of external circumstances. Thus, police officers should have knowledge of the emotional sphere and emotional intelligence, which play an important role in developing skills of effective communication and constructive response in conflict and emergency situations.
Keywords: emotions; emotional sphere; affective processes; emotional intelligence; intellectual-emotional activity; personality; police